2016
DOI: 10.1080/15384047.2016.1210741
|View full text |Cite
|
Sign up to set email alerts
|

The role of adipose stem cells in inflammatory bowel disease: From biology to novel therapeutic strategies

Abstract: Inflammatory bowel diseases are an increasing phenomenon in western countries and in growing populations. The physiopathology of these conditions is linked to intestinal stem cells homeostasis and regenerative potential in a chronic inflammatory microenvironment. Patients with IBD present an increased risk of developing colorectal cancer (CRC), or colitis associated cancer (CAC). Conventional treatment for IBD target the inflammatory process (and include anti-inflammatory and immunosuppressive drugs) with biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 96 publications
0
24
0
1
Order By: Relevance
“…The intestinal epithelium of IBD patients undergoes repeated cycles of injury and repair in response to chronic, recurring inflammation. 47 We found decreased SIRT2 expression in the intestinal epithelium from patients with IBD. In addition, we show that SIRT2 deficiency exhibits enhanced epithelial proliferation in mice.…”
Section: Discussionmentioning
confidence: 67%
“…The intestinal epithelium of IBD patients undergoes repeated cycles of injury and repair in response to chronic, recurring inflammation. 47 We found decreased SIRT2 expression in the intestinal epithelium from patients with IBD. In addition, we show that SIRT2 deficiency exhibits enhanced epithelial proliferation in mice.…”
Section: Discussionmentioning
confidence: 67%
“…Due to their high therapeutic potential, ASCs are now considered an indispensable tool in regenerative medicine [61][62][63][64]. Studies have shown the successful treatment with ASCs for many disease including graft-versus-host disease [65], wound healing [66], cardiovascular [67], inflammatory bowel disease [68], diabetes mellitus [69] and several injuries including kidney and spinal cord [70], bone and craniofacial reconstruction [71,72], liver cirrhosis [73], multiple sclerosis [74]. In addition to their self-renewal ability, ASCs have the ability to differentiate into multiple lineages, including adipocytes, osteoblasts, chondrocytes, and endothelial cells [75,76].…”
Section: Is There a Role Of Adipose-derived Stem Cells (Asc) In Lipedmentioning
confidence: 99%
“…The role of stem cells has been already intensively researched [85,86], even in inflammatory bowel diseases [87], but these potent cells have raised interest about their role or potential use in IBS.…”
Section: New Hypothesesmentioning
confidence: 99%